Cardiac autonomic functions and the emergence of violence in a highly realistic model of social conflict in humans - Haller, Jozsef; Raczkevy-Deak, Gabriella; Gyimesine, Katalin P.; Szakmary, Andras; Farkas, Istvan; Vegh, Jozsef (Frontiers in Behavioral Neuroscience, 2014)
Among the multitude of factors that can transform human social interactions into violent conflicts, biological features received much attention in recent years as correlates of decision making and aggressiveness especially in critical situations. We present here a highly realistic new model of human aggression and violence, where genuine acts of aggression are readily performed and which at the same time allows the parallel recording of biological concomitants. Particularly, we studied police officers trained at the International Training Centre (Budapest, Hungary), who are prepared to perform operations under extreme conditions of stress. We found that aggressive arousal can transform a basically peaceful social encounter into a violent conflict. Autonomic recordings show that this change is accompanied by increased heart rates, which was associated earlier with reduced cognitive complexity of perceptions ("attentional myopia") and promotes a bias towards hostile attributions and aggression. We also observed reduced heart rate variability in violent subjects, which is believed to signal a poor functioning of prefrontal-subcortical inhibitory circuits and reduces self-control. Importantly, these autonomic particularities were observed already at the beginning of social encounters i.e. before aggressive acts were initiated, suggesting that individual characteristics of the stress-response define the way in which social pressure affects social behavior, particularly the way in which this develops into violence. Taken together, these findings suggest that cardiac autonomic functions are valuable external symptoms of internal motivational states and decision making processes, and raise the possibility that behavior under social pressure can be predicted by the individual characteristics of stress responsiveness.